1982
DOI: 10.1038/bjc.1982.107
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt-type lymphoma in France among non-Hodgkin malignant lymphomas in Caucasian children

Abstract: In a retrospective analysis of 87 cases of Caucasian childhood non-Hodgkin malignant lymphoma (NHML) from Lyon, France, all the case were diffuse lymphomas, but 47 were diagnosed as monomorphic small non-cleaved NHML, pathologically indistinguishable from Burkitt's lymphoma (BL). BL could then be the most frequent childhood lymphoma in France. This homogeneous series allows better definition of the characteristics of BL within NHML. Age distribution is similar to that of endemic BL, with a sex ratio of 3.7/1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 23 publications
(16 reference statements)
2
14
0
1
Order By: Relevance
“…13a A histologically indistinguishable disease with an about 20-fold lower incidence and mainly abdominal presentation was also found all over the world of which only about 15% of the cases harbor the EBV genome. 14,15 The incidence of BL increased strongly in the western countries with the advent of the HIV epidemics in the eighties 16 of which about 40% of the cases are associated with EBV. 17 Regardless of its geographical origin and its association with EBV, BL is invariably characterized by specific recurrent reciprocal chromosomal translocations involving the long arm of chromosome 8 carrying the c-myc gene and one of the immunoglobulin (Ig) heavy or light chain loci on chromosome 14 (heavy chain), 2 or 22 (j or k light chain).…”
mentioning
confidence: 99%
“…13a A histologically indistinguishable disease with an about 20-fold lower incidence and mainly abdominal presentation was also found all over the world of which only about 15% of the cases harbor the EBV genome. 14,15 The incidence of BL increased strongly in the western countries with the advent of the HIV epidemics in the eighties 16 of which about 40% of the cases are associated with EBV. 17 Regardless of its geographical origin and its association with EBV, BL is invariably characterized by specific recurrent reciprocal chromosomal translocations involving the long arm of chromosome 8 carrying the c-myc gene and one of the immunoglobulin (Ig) heavy or light chain loci on chromosome 14 (heavy chain), 2 or 22 (j or k light chain).…”
mentioning
confidence: 99%
“…In a recent histopathological study from Algeria (Afiane & Chouiter, 1982), it was reported that BL represents 46.5% of all childhood NHML, in comparison with the 56% reported by Philip et al (1980bPhilip et al ( , 1982 and the 45.6% reported by GerardMarchant et al (1982) in France and the 33% reported by Cosmann & Berard (1980) (Dorfmann, 1965;Levine et al, 1982;Philip et al, 1982). During the period [1980][1981][1982] Abdominal Burkitt-type lymphoma is a clear clinical entity accounting for at least 60% of all Burkitt lymphomas in Algerian children.…”
Section: Discussionmentioning
confidence: 73%
“…therapy and the use of high-dose cytarabine (LMB 86). Before this, results in patients with CNS disease were disappointing, despite the use of craniospinal irradiation with chemotherapy regimen, which was very effective in less advanced disease (Philip et al, 1982;Chilcote et al, 1991). The subsequent results with LMB 86 were dramatic, with a survival rate over 70% (Rubie et al, 1988).…”
mentioning
confidence: 99%
“…The cure rate has increased from less than 20% before 1980 (Al-Attar et al, 1979) to over 70% in the 1980s and 1990s (Philip et al, 1982;Al-Attar et al, 1986;Patte et al, 1990). Recent studies have concentrated on improving outcome in the remaining poor-risk subgroups (Hann et al, 1988;Patte et al, 1991;Cairo et al, 1996), reducing early deaths by aggressive treatment of early renal and infectious complications (Lynch et al, 1977;Allegretta et al, 1985) and avoiding debulking surgery (Frappaz et al, 1988;Al-Attar et al, 1989).…”
mentioning
confidence: 99%